Blood–Brain Barrier Dysfunction in Mild Traumatic Brain Injury: Evidence From Preclinical Murine Models - Wu, Yingxi; Wu, Haijian; Guo, Xinying; Pluimer, Brock; Zhao, Zhen (Frontiers in Physiology, 2020)
Mild traumatic brain injury (mTBI) represents more than 80% of total TBI cases and is a robust environmental risk factor for neurodegenerative diseases including Alzheimer’s disease (AD). Besides direct neuronal injury and neuroinflammation, Blood-brain barrier (BBB) dysfunction is also a hallmark event of the pathological cascades after mTBI. However, the vascular link between BBB impairment caused by mTBI and subsequent neurodegeneration remains undefined. In this review, we focus on the preclinical evidence from murine models of BBB dysfunction in mTBI and provide potential mechanistic links between BBB disruption and the development of neurodegenerative diseases.